Immunohistochemically Detected High Expression of Matrix Metalloproteinase-2 as Predictor of Poor Prognosis in Duke’s B Colon Cancer - Šundov, Željko (Croatian Medical Schools, 2008)
AIM: To demonstrate immunohistochemical expression of matrix metalloproteinase-2 (MMP-2) protein in Duke’s B colon cancer and determine its correlation with age, sex, grade, presence of vascular invasion, and patients’ overall survival. METHOD: The study took place from January 1995 to December 1997. We determined the expression of MMP-2 in 152 formalin-fixed, paraffin embedded specimens of Duke’s B colon carcinomas by immunohistochemical analysis using MMP-2 monoclonal antibody. Immunohistochemical expresssion was scored semiquantitatively. Carcinomas were graded as low or high grade. Survival time was analyzed with Kaplan-Meier method, and the log-rank test was used to assess the differences between groups. Cox proportional hazard regression model was used for multivariate survival analysis. RESULT: Univariate analysis showed that positive staining for MMP-2, high histological grade, vascular invasion, male sex, and age >60 years were associated with shorter survival in patients with Duke’s B colon cancer (P range from 0.023 to <0.001). Multivariate analysis showed that only MMP-2 overexpression (P < 0.001; hazard ratio [HR] = 3.64) and vascular invasion (P < 0.001; HR = 4.27) were associated with shorter overall survival. CONCLUSION: Expression of MMP-2 is an important independent indicator of shorter survival in patients with Duke’s B colon cancer and should be taken into consideration in decision-making on the use of adjuvant systemic therapy in patients with Duke’s B colon cancer.